Impact of herbicides on beneficial arthropods associated with cotton - Soares, José Janduí; Braz, Benedito Aparecido; Busoli, Antonio C. (Pesquisa Agropecuaria Brasileira, 1995)
In order to study the impact of herbicides on beneficial arthropods associated with cotton, a trial was placed at Jaboticabal, SP, Brazil, in 1993/94. The experimental design was a complete randomized block with four replications and six treatments: 1) weed-free control; 2) control without hoe weeding; 3) control with grass; 4) MSMA (Monosodium methanearsonate acid) 2.4 kg a.i./ha; 5) fluazyfop-p-butil 0.50 kg a.i./ha; and 6) haloxyfop-metil 0.12 kg a.i./ha. The results showed that the herbicides MSMA and fluazyfop-p-butil affected Cycloneda sanguinea and MSMA affected Doru fineare. The presence of broad leave weed was favorable to Cycloneda sanguinea, while the grass was favorable to Doru fineare.